2021
DOI: 10.1002/mar.21532
|View full text |Cite
|
Sign up to set email alerts
|

Examining the effects of robots' physical appearance, warmth, and competence in frontline services: The Humanness‐Value‐Loyalty model

Abstract: Because of continuous improvements in their underlying technologies, customers perceive frontline robots as social actors with a high level of humanness, both in appearance and behavior. Advancing from mere theoretical contributions to this study field, this article proposes and empirically validates the humanness‐value‐loyalty model (HVL model). This study analyzes to what extent robots' perceived physical human‐likeness, perceived competence, and perceived warmth affect customers' service value expectations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
144
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 176 publications
(156 citation statements)
references
References 126 publications
(203 reference statements)
9
144
2
1
Order By: Relevance
“…The study findings revealed that service robot attributes, including competence, role significance, warmth, social presence, adaptability and autonomy, determine value facilitation. This extends recent studies on service robot attributes that aid in customer value co-creation (Akdim et al , 2021; Belanche et al , 2021; Qiu et al , 2020). Additionally, guest value co-creation mediates the effect of value facilitation on advocacy intentions ( H1 and H2 ).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The study findings revealed that service robot attributes, including competence, role significance, warmth, social presence, adaptability and autonomy, determine value facilitation. This extends recent studies on service robot attributes that aid in customer value co-creation (Akdim et al , 2021; Belanche et al , 2021; Qiu et al , 2020). Additionally, guest value co-creation mediates the effect of value facilitation on advocacy intentions ( H1 and H2 ).…”
Section: Discussionsupporting
confidence: 82%
“…The findings of the qualitative study revealed that six service robot attributes, including role significance, competence, social presence, autonomy, warmth and adaptability, are critical in facilitating the guest experience during the value co-creation process in the restaurant. While the identification of service robot attributes such as competence, warmth and social presence is consistent with the past research (Belanche et al , 2021; Chang and Kim, 2022; Yoganathan et al , 2021), autonomy, adaptability and role significance have received less attention in the previous literature. Furthermore, the findings reveal that guest interaction comfort plays a key role in determining guest interaction with service robots in restaurants.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…In contrast, service robots with discomforting appearances and features may evoke negative consumer reactions, such as objection to use (Gursoy et al , 2019) and lack of genuine interactions (Shin and Jeong, 2020). Considering the mixed findings in the literature and the fact that many AI service robots possess anthropomorphic features such as humanlike appearances to simulate humanlike emotions and behaviors (Belanche et al , 2021), it is important to investigate the effects of anthropomorphic features of service robots on consumer perceptions and acceptance.…”
Section: Literature Reviewmentioning
confidence: 99%